Recent Development in Copper based Hole Transport Materials for Emerging Inverted Perovskite Solar Cells. Issue 1 (April 2021) - Kumar, Anjan; Singh, Sangeeta; Yadav, Anupam
Abstract: In the photovoltaic (PV) research community, the dramatic improvement in the power conversion efficiency of organic-inorganic metal halide perovskite-based devices has made them very appealing. The serious challenge, though, has to do with durability under different circumstances and difficulties with toxicity. In recent years, a significant number of papers have been published in PSCs based on these issues through the use of different electron transport materials(ETMs), hole transport materials (HTMs), and Perovskite materials. The hole transport material is responsible for a significant part of the expense of the components of a Perovskite solar cell (PSC), as the most effective systems so far have costly HTMs, such as spiro-OMeTAD and poly(triaryl amine). The inverted PSCs (p-i-n) give a wide variety of alternate HTLs, as the HTL is deposited underneath the perovskite layer. Any material with moderate hole mobility is, therefore, a possible substitute for replacing the expensive HTMs that have been used so far. In this review manuscript, we have compiled the various Cu-based materials added as HTMs in planar inverted p-i-n) structure. This manuscript appears to focus on the role and classification of various copper-based materials used as a hole transport layer affecting long-term stability, improving solar cell parameters, and thus improving overall device performance. Furthermore, a description of the overall device structure, preparation methods, and the effect of the thickness of the HTM layers on the overall solar cell parameters of the perovskite devices is also presented. We hope that this analysis will explicitly and extensively demonstrate their significance and strengths in the concerned domain by introducing and exploring the developments of Cu-based materials as HTMs in planar PSCs and provide inspiration for their further development.